A return of devotion - Hunter, Kristi Ann (Hunter, Kristi Ann. Haven Manor, 2019)
"When ownership of the estate where Daphne Blakemoor works passes to William, Marquis of Chemsford, her quiet, secluded life is threatened. William has a connection to her youth--and they've both been hiding from the past. Can they face their deepest wounds and forge a new path for the future?" --